Role of Forensics in the Cases of Criminal Poisoning - Franjić, Siniša (American International Journal of Multidisciplinary Scientific Research, 2018)
Forensics is a scientific discipline which deals with evidencing of criminal acts, and consists of a series of sub disciplines. One of them is forensic toxicology whose task is to detect the existence of poisons in the human body and existence of poisons in all areas where they should not be. Although rarely happens, the criminal act of Poisoning has to be investigated in accordance with the rules of criminal investigation and, due to the established facts, to raise the indictment and punish the perpetrator.